Colorectal malignancy in the younger non-screened age group – A national study: Colorectal malignancy in the younger non-screened age group - Sammut, Mark; Sammut, Matthew; Farrugia, Melanie; Gatt, Jurgen; Spiteri, Neville; Gatt, Noel (Journal of Surgery and Medicine, 2025)
Background/Aim: Colorectal cancer (CRC) continues to be a significant public health issue. There is growing concern that the incidence rate for CRC in adults under 55 years of age is on the rise. This study aimed to identify the trends in incidence rates for CRC cases among the non-screened adult population. Methods: All patients, aged between 18 and 55 years, who were diagnosed and underwent colorectal resections for histologically confirmed CRC between January 2010 and December 2023, were identified and included in the data set. Results: A total of 162 patients under the age of 55 were diagnosed and operated on for CRC, with an even gender distribution of 81 males (50%) and 81 females (50%). The median age was 44 years (range: 18 to 55 years). No significant statistical difference was detected between female and male patients in terms of median age (P=0.41), both had a median age of 45 years. The total amount of CRC tumors diagnosed per year in patients under 55 averaged about 12.00 cases (mean=11.58 cases per year). There appeared to be a slight trend of increasing incidence by 0.36 cases per year. No significant statistical differences were found in relation to tumor location, tumor stage, and gender (P=0.93, P=0.11). The median survival period was 32.15 months (range: 1–112 months). Conclusion: The incidence of CRC in younger, non-screened patients was found to be on the rise in our local population. Clinicians need to be vigilant for CRC in younger individuals. Additionally, early investigations may need to be undertaken within this age group.